A conserved malaria parasite antigen Pb22 plays a critical role in male gametogenesis in Plasmodium berghei. (10th December 2020) - Liu, Fei; Yang, Fan; Wang, Yaru; Hong, Minsheng; Zheng, Wenqi; Min, Hui; Li, Danni; Jin, Ying; Tsuboi, Takafumi; Cui, Liwang; Cao, Yaming
Abstract: Gametogenesis, the formation of gametes from gametocytes, an essential step for malaria parasite transmission, is targeted by transmission‐blocking drugs and vaccines. We identified a conserved protein (PBANKA_0305900) in Plasmodium berghei, which encodes a protein of 22 kDa (thus named Pb22 ) and is expressed in both asexual stages and gametocytes. Its homologues are present in all Plasmodium species and its closely related, Hepatocystis, but not in other apicomplexans. Pb22 protein was localised in the cytosols of schizonts, as well as male and female gametocytes. During gamete‐to‐ookinete development, Pb22 became localised on the plasma membranes of gametes and ookinetes. Compared to the wild‐type (WT) parasites, P. berghei with pb22 knockout (KO) showed a significant reduction in exflagellation (~89%) of male gametocytes and ookinete number (~97%) during in vitro ookinete culture. Mosquito feeding assays showed that ookinete and oocyst formation of the pb22 ‐KO line in mosquito midguts was almost completely abolished. These defects were rescued in parasites where pb22 was restored. Cross‐fertilisation experiments with parasite lines defective in either male or female gametes confirmed that the defects in the pb22 ‐KO line were restricted to the male gametes, whereas female gametes in the pb22 ‐KO line were fertile at the WT level. Detailed analysis of male gametogenesis showed that 30% of the male gametocytes in the pb22 ‐KO line failed to assemble the axonemes, whereas ~48.9% of the male gametocytes formed flagella but failed to egress from the host erythrocyte. To explore its transmission‐blocking potential, recombinant Pb22 (rPb22) was expressed and used to immunise mice. in vitro assays showed that the rPb22‐antisera significantly inhibited exflagellation by ~64.8% and ookinete formation by ~93.4%. Mosquitoes after feeding on rPb22‐immunised mice also showed significant decreases in infection prevalence (83.3–93.3%) and oocyst density (93.5–99.6%). Further studies of the Pb22 orthologues in human malaria parasites are warranted.